Friday
March 24, 2017

Post a New Question

Posted by on Wednesday, December 7, 2011 at 1:33am.

Solve by completing the square.

a² - 2√(3a) + 2 = 0


Solve for x. I don't know if you can use completing the square for this problem.

ax^n + b = 0

  • Algebra 2 - , Wednesday, December 7, 2011 at 6:39am

    suspect you mean
    a^2 -2 a sqrt 3 = -2

    half of 2 sqrt 3 squared is 3 so add 3 to both sides

    a^2 -2 a sqrt 3 + 3 = 1

    (a-sqrt 3)^2 = 1

    a = sqrt 3 +/-1

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question